Rate of rebound in follicle growth after cessation of ovarian stimulation in initial non‐responders: a prospective cohort study - Gleicher, Norbert (J Ovarian Res, 2021)
Previously anecdotally observed rebounds in follicle growth after interruption of exogenous gonadotropins in absolute non-responders were the impetus for here reported study. In a prospective cohort study, we investigated 49 consecutive patients, absolutely unresponsive to maximal exogenous gonadotropin stimulation, for a so-called rebound response to ovarian stimulation. A rebound response was defined as follicle growth following complete withdrawal of exogenous gonadotropin stimulation after complete failure to respond to maximal gonadotropin stimulation over up to 5–7 days. Median age of study patients was 40.5 ± 5.1 years (range 23–52). Women with and without rebound did not differ significantly (40.0 ± 6.0 vs. 41.0 ± 7.0 years, P = 0.41), with 24 (49.0%) recording a rebound and 25 (51.0%) not. Among the former, 21 (87.5%) reached retrieval of 1–3 oocytes and 15 (30.6%) reached embryo transfer. A successful rebound in almost half of prior non-responders was an unsuspected response rate, as was retrieval of 1–3 oocytes in over half of rebounding patients. Attempting rebounds may, thus, represent another incremental step in very poor prognosis patients before giving up on utilization of autologous oocytes. Here presented findings support further investigations into the underlying physiology leading to such an unexpectedly high rebound rate.